DETERMINANTS OF RETURN ON ASSETS OF BANKING SECTOR IN INDONESIA: CASE STUDY ON 19 COMMERCIAL BANKS IN INDONESIA FROM 2008 TO 2017 - Mahmudi, Ilham Muharam; Anggono, Achmad Herlanto (Journal of Business and Management, 2018)
Abstract. It is recorded during the period of 2008 to 2017, 3 major banks in this research sample has changed its ownership to foreign-owned. While their asset categorized as foreign-owned, the asset growth of both domestic and foreign banks is still increasing despite the tightening competition from foreign banks. The determinants being observed in the research are CAR, LDR, FED, NPL, NIM, Bank Size, BOPO, CRDTA, INFL, and GDP with the dependent variable is ROA. This research used the sample of 19 commercial banks categorized as BACB 3 and BACB 4 over the period of 2008 to 2017. The result found out that NPL, BOPO, and GDP are having a negatively significant relationship to the banks’ profitability. While CAR, LDR, NPL, NIM, LNSIZE, and Inflation Rate found to be positive and significantly correlated with the profitability of the bank.Keywords: Commercial Bank, Determinant, Foreign Ownership, Return on Assets, Panel Data Regression